Molecular Identification and In-Vitro Screening of the Isolated Rhizobacteria Against Rhizoctonia solani - Lopez, Lani Lou Mar Agoy (International Journal on Food, Agriculture and Natural Resources, 2025)
Abstract—this study determined the in vitro effect of isolated rhizobacteria from rice rhizosphere against the rice fungal pathogen Rhizoctonia solani. The antagonistic effects of rhizobacteria against R. solani were assessed using the dual culture technique and scanning electron microscopy for the mode of action and interaction. Among the nine rhizobacteria isolates, 7 belong to the genus Bacillus and one belongs to the genus Lysinibacillus while one isolate RM-W3-5 is unknown. The rhizobacterium were identified as B. pumilus, B. megaterium ,B. cereus, B. amyloliquefaciens ,Bacillus sp., B. rhizosphaerae, B. clausii and L. macroides. Results of dual culture technique of the rhizobacterial isolates inhibit the mycelial growth of R. solani from 8.9% up to 82.61%. Highest mycelial growth inhibition (MGI) of 82.61% was obtained from R. solani paired with B. pumilus while lowest MGI of 8.9% was obtained from B. clausii. The interactions between RM-W3-5 and B. pumilus against R. solani were tested using scanning electron microscope (SEM), the two isolates were selected because of their promising performance on the dual culture assay. Isolate RM-W3-5 paired to R. solani showed the structural alterations such as shrinking, shrivelling of the hyphae and hyphal disintegration. Similar occurrence was observed when R. solani was paired with B. pumilus. The results of the present study suggest that B. pumilus and RM-W3-5 is potential biological control agent against R. solani. However, supplementary analysis has to be done to validate the potential of these rhizobacteria.